Human tripartite motif 5alpha domains responsible for retrovirus restriction activity and specificity - Perez-Caballero, David; Hatziioannou, Theodora; Yang, Annie; Cowan, Simone; Bieniasz, Paul D (Journal of virology, 2005)
The tripartite motif 5alpha protein (TRIM5alpha) is one of several factors expressed by mammalian cells that inhibit retrovirus replication. Human TRIM5alpha (huTRIM5alpha) inhibits infection by N-tropic murine leukemia virus (N-MLV) but is inactive against human immunodeficiency virus type 1 (HIV-1). However, we show that replacement of a small segment in the carboxy-terminal B30.2/SPRY domain of huTRIM5alpha with its rhesus macaque counterpart (rhTRIM5alpha) endows it with the ability to potently inhibit HIV-1 infection. The B30.2/SPRY domain and an additional domain in huTRIM5alpha, comprising the amino-terminal RING and B-box components of the TRIM motif, are required for N-MLV restriction activity, while the intervening coiled-coil domain is necessary and sufficient for huTRIM5alpha multimerization. Truncated huTRIM5alpha proteins that lack either or both the N-terminal RING/B-Box or the C-terminal B30.2/SPRY domain form heteromultimers with full-length huTRIM5alpha and are dominant inhibitors of its N-MLV restricting activity, suggesting that homomultimerization of intact huTRIM5alpha monomers is necessary for N-MLV restriction. However, localization in large cytoplasmic bodies is not required for inhibition of N-MLV by huTRIM5alpha or for inhibition of HIV-1 by chimeric or rhTRIM5alpha.